Pengaruh Discovery Learning Terhadap Upaya Pengembangan Keterampilan Komunikasi Siswa: Studi Literatur - Nugrahaningtyas, Irma Yunita; Rohmah, Lutfiah Nur; Defitasari, Aisah (Indo-MathEdu Intellectuals Journal, 2024)
Communication skills are one of the skills that students really need. Students' communication skills can be developed using discovery learning methods. The discovery learning method trains students to be more active in learning activities. This research aims to describe efforts to improve communication using discovery learning methods. The type of research we use is literature study sourced from various journals and articles obtained by searching for topic-related data in academic databases by searching for relevant keywords then accessing them online on the official website of scientific journals or digital libraries and then analyzing the data contained in the articles. and journals according to research needs. This research proves that the discovery learning method has proven to be effective and able to improve students' communication skills. This is because the discovery learning method focuses more on the child's own activity, so it is not impossible that children will hone their communication skills even more. Children will be encouraged to search for material, exchange material, and express opinions. The teacher will act as a facilitator